Tuwim’s Dialogues with Banality - Bocheński, Tomasz (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2017)
The article examines the relation between Tuwim’s poetry and modern colloquial language. The avant-garde artists for whom in the beginning of the 20th-century art was an elite occupation, treated every-day speech as a mass form of communication. Tuwim’s poetry was frequently criticised for banality. Matywiecki presents the poet as a hero fighting with the demon of commonness. The crucial thesis of the article is that banality which is modified in a creative way says more about the epoch than elitist visions. In his poetry, satire and cabaret work Tuwim transformed triviality into dialog and a common human being into a creative person. Transition of the street talk into original speech is the defence against reducing individual being to cliché which means the fear of 20th-century killing ideologies.